Non-halogenated Ionic Liquid Dramatically Enhances Tribological Performance of Biodegradable Oils - Rohlmann, Patrick; Munavirov, Bulat; Furó, István; Antzutkin, Oleg; Rutland, Mark William; Glavatskih, Sergei (Frontiers in Chemistry, 2019)
Ionic liquids open the possibility of tribotronic control – the ability to select either the anion or cation at the surface and tune the corresponding interfacial film structure and thus the friction of the system. Conventional, halogenated ionic liquids are unsuitable for such applications due to toxicity of the species produced during tribochemical reactions. Similarly, there is increasing pressure to replace conventional lubricant oils with biodegradable ones for reasons of sustainablility. We show that a phosphonium orthoborate ionic liquid, if added to biodegradable oils, reduces the wear of steel surfaces by up to 92% compared to the neat oils at 90C. It is shown that the ionic liquid is preferentially adsorbed and, that the reduction in wear can be traced to the formation of complex boron enriched patches of boundary films during shear.